Impact of Cathode Variations on the Mechanical Properties of Hard Anodizing in Sulfuric Acid 15% and Phosphoric Acid 1% - Sihombing, Rony Pasonang (Jurnal Internasional Penelitian Teknologi Terapan, 2024)
Aluminum 1100 could be used as domestic appliances material, especially on kitchen equipment. The purpose of this research was to improve the properties of aluminum 1100. In order to improve the physical and mechanical properties, a hard anodizing process was conducted. In the hard anodizing process, 1100 aluminum workpieces are sanded, decreased in alkaline solution and neutralized in acidic solution. The hard anodizing process is carried out by placing the workpiece on the positive pole and the electrode on the negative pole (cathode) of the direct current source. The hard anodizing process of 1100 aluminum alloy was carried out in a mixture of 15% sulfuric acid and 1% phosphoric acid solution, current density of 3A/dm2, anodizing time of 30 minutes, temperature of 5 °C, and cathode variation (Al and Pb). The results showed the formation of an oxide layer on the metal surface consisting of two types of layers, called the barrier layer and the porous layer. The barrier layer has no pores because it has conductive microstructure properties and reaches the maximum thickness. The porous layer formed can increase the overall thickness of the oxide layer, while the barrier layer remains a constant thickness and increases the hardness level of the aluminum. This study resulted in a process efficiency of 83.04% with the best oxide layer thickness of 11.43 μm and the highest hardness of 144.25 HVNoxide layer thickness of 11.43 μm and the highest hardness of 144.25 HVN.